Occult cerebral hemorrhage induced by high-dose oral methanol poisoning: a case report - Tang, Yuncheng; Liang, Pengfei; Fang, Qiming; Zhao, Juan; Zhang, Li; Zhang, Xiaolin; Tang, Haowen; Jiang, Yu; Zhao, Zhiwen; Wang, Bo; Fang, Zhicheng (Frontiers in Pharmacology, 2026)
BackgroundAcute methanol intoxication is life-threatening and typically presents with severe metabolic acidosis and central nervous system injury. Intracranial hemorrhage associated with methanol poisoning is uncommon and may be clinically occult, potentially delaying diagnosis and intervention.CaseWe report a case of high-dose oral methanol poisoning presenting with profound metabolic acidosis and coma. Emergent cranial CT revealed basal ganglia hemorrhage. The patient underwent intermittent hemodialysis and received supportive pharmacotherapy. Owing to obstructive hydrocephalus and neurological deterioration, frontal burr-hole drilling and ventricular drainage were performed. Although metabolic derangements partially improved, the patient remained comatose after 1 week of hospitalization. The family requested transfer to another hospital for further management; however, the patient died during inter-hospital transport.ConclusionCerebral hemorrhage secondary to methanol poisoning can be insidious and may occur within hours to days after ingestion. Early neuroimaging and timely intervention are crucial when neurological deterioration or hydrocephalus is suspected.